Hartman-Cox : Selected and current works - Dobney, Stephen., author; Hartman-Cox Architects (Mulgrave, Vic. : Images Pub. Group, 1994)
THE MASTER ARCHITECT SERIES is a series of monographs on some of the greatest architects and architectural firms of our time. Each monograph will contain 256 pages displaying several hundred color photographs, drawings, sketches and renderings. Although primarily a pictorial essay, the books will contain selected projects described in concise detail, along with a critique or overview of the firm, a resume of the partners, and a comprehensive bibliography.
Includes bibliographical references (pages 248-253) and index.
Keywords: Hartman-Cox Architects -- Catalogs; Architecture -- Catalogs -- History -- 20th century -- United States; Architecture -- History -- 20th century -- United States